TINJAUAN TENTANG PENGAWASAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PADA SD NEGERI 002 BATU AMPAR KECAMATAN BATU AMPAR KABUPATEN KUTAI TIMUR - Melisa Ardiyanti (ADMINISTRASI PUBLIK, 2020)
Schools need tools that act as administrators and dynamisators so that the goals can be effectively and efficienty achieved. An important element that contributes to theachieving of the overall pupose of the activity in education management at school is supervision, which is governed by the headmaster. One aspect of the surveillance is the teacher’s performance. The purpose of this study was to find out how the headmaster conducted oversight in improving teacher’s performance at SDN 002 Batu Ampar Sub-district of Batu Ampar,Regency of Kutai Timur. The focus of this study is the headmaster”s internal superveillance by direct inpection, indirect place observations annd field reports and surveillance in order to observeattendance and reprts from the vice. This method of research is a qualitative deskriptive study method, which became the source id the study of the principal as key informant and teacher’s as a support informant. By using data collection techniques, the observation annd documentary studies, by data collection, data reduction, data presention, and data insention. The results of this study suggest that the performance of the headmaster’s supervision of both direct and indirect supervision is good enough only to have a maximum. A teacher’s performanceis also good enough, it just still needs the pricipal’s guidabce in with RPP and sylabus work and teachers to increase his skills and creativity in teaching so that classroom interaction become maximum.